Fumigant toxicity of Tagetes filifolia Lag essential oil and its main compounds against Tribolium castaneum Herbs and its relation to lipid peroxidation - Olmedo, Rubén Horacio (2015)
The development of natural insecticides would help to decrease the negativeimpact of synthetic insecticides. Fumigant toxicity of essential oil of Tagetesfilifolia Lag (Asterales: Asteraceae) and its major compounds were evaluatedagainst Tribolium castaneum Herbst (Coleoptera: Tenebrionidae). Theessential oils were analyzed by gas chromatography?mass spectrometry. Theessential oil and (E)-anethole were the most toxic at 24 h against adult insects(CL50= 2.4 y 2.6 µL/mL water, respectively). Changes in the products of lipidperoxidation were evidenced by an increase in malondialdehyde content.Acetylcholinesterase activity in vitro, of T. castaneum adults, was also reported.(E)-anethole and estragole showed similar acetylcholinesterase inhibition (54and 63%, respectively at 5 mM). The present study constitutes one of the firstcontributions to understanding the relationship between the insecticidal actionof essential oil and oxidative stress.